UNMASKING TUBERCULOUS MENINGOENCEPHALITIS: A CASE OF LATENT TB REACTIVATION WITH NEUROLOGICAL MANIFESTATIONS (Journal of Medical & Health Sciences Review, 2025)
Background: Tuberculosis (TB) remains a major global health concern, particularly in high-burden countries like Pakistan. Central nervous system (CNS) TB, including tuberculous meningitis (TBM) and the rarer tuberculous encephalitis (TB-E), is associated with significant morbidity and mortality. Diagnosis is often delayed due to nonspecific symptoms and low sensitivity of standard diagnostic tests.Case Presentation: We describe a 23-year-old male with a history of treated Hepatitis C who presented with three months of fever, cough, and weight loss, followed by worsening headache and vomiting. Initial investigations, including sputum AFB and chest X-ray, were negative. Laboratory results showed leukocytosis, elevated CRP and ESR, and sterile cultures. CSF analysis revealed lymphocytic pleocytosis, high protein, and normal glucose. Despite negative CSF GeneXpert, AFB smear, and fungal tests, a high clinical suspicion for CNS TB persisted due to a positive TB spot test and neurological signs, including abducens nerve palsy. Antiviral therapy failed to improve symptoms. Given the endemic setting and clinical picture, empirical anti-tuberculous therapy (ATT) was initiated. The patient responded rapidly with the resolution of symptoms and regained 10 kg over three months. He completed six months of ATT with no recurrence.Conclusion: This case underscores the diagnostic challenges of CNS TB in endemic areas. When standard tests are inconclusive, clinical judgment and early empirical ATT can be lifesaving. High clinical suspicion and prompt treatment are crucial to prevent severe neurological outcomes in suspected TB-E cases.